Proceedings of the 2nd International Conference on Internet of Things, Big Data and Security 2017
DOI: 10.5220/0006304103020308
|View full text |Cite
|
Sign up to set email alerts
|

A Cognitive-IoE Approach to Ambient-intelligent Smart Home

Abstract: In today's world, we are living in busy metropolitan cities and want our homes to be ambient intelligent enough towards our cognitive requirements for assisted living in smart space environment and an excellent smart home control system should not rely on the users' instructions. Cognitive IoE is a new state-of-art computing paradigm for interconnecting and controlling network objects in context-aware perception-action cycle for our cognitive needs. The interconnected objects (sensors, RFID, network objects et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Context aware computing. Jamnal et al [38] have proposed a new form of ambient intelligent architecture for smart homes by anticipating occupant's intentions for understanding purpose. This is achieved with a combined knowledge from traditional context aware pervasive systems and present epoch of CIoT technologies.…”
Section: Cognitive Agentsmentioning
confidence: 99%
“…Context aware computing. Jamnal et al [38] have proposed a new form of ambient intelligent architecture for smart homes by anticipating occupant's intentions for understanding purpose. This is achieved with a combined knowledge from traditional context aware pervasive systems and present epoch of CIoT technologies.…”
Section: Cognitive Agentsmentioning
confidence: 99%
“…AmI and CIoT are intertwined, with overlapping application scenarios [ 8 , 9 , 10 , 11 ]. Although the distinction between the terms may be subtle, Jamnal and Liu [ 12 ] argue that CIoT extends the capabilities of AmI in smart environments, going beyond monitoring and supporting people’s tasks to proactively influencing users’ plans and intentions.…”
Section: Introductionmentioning
confidence: 99%
“…Groupu_agent 5 proposition:[12, 76] backed ranges: [1/1][2/4] → forward proposition u_agent 6 proposition:[43, 100] backed ranges: [1/1][4/4] → forward proposition Round 1-Group 2 u_agent 3 proposition: [82, 100] backed ranges: [0/1][2/4] → broaden range [74, 100] u_agent 4 proposition: [43, 67] backed ranges: [0/1][3/4] → forward proposition u_agent 3 proposition: [74, 100] backed ranges: [0/1][3/4] → forward proposition u_agent 4 proposition: [43, 67] backed ranges: [0/1][3/4] → forward proposition Round 1/2-Group 1 u_agent 1 proposition: [88, 96] backed ranges: [0/1][2/4] → broaden range [76, 96] u_agent 2 proposition: [59, 71] backed ranges: [0/1][3/4] → forward proposition u_agent 1 proposition: [76, 96] backed ranges: [0/1][3/4] → forward proposition u_agent 2 proposition: [59, 71] backed ranges: [0/1][3/4] → forward proposition Round 2-Group 2 u_agent 3 proposition: [74, 100] backed ranges: [0/1][3/4] → forward proposition u_agent 4 proposition: [43, 67] backed ranges: [0/1][3/4] → broaden range [43, 73] u_agent 3 proposition: [74, 100] backed ranges: [0/1][3/4] → broaden range [72, 100] u_agent 4 proposition: [43, 73] backed ranges: [0/1][3/4] → forward proposition u_agent 3 proposition: [72, 100] backed ranges: [1/1][3/4] → forward proposition u_agent 4 proposition: [43, 73] backed ranges: [1/1][3/4] → forward proposition Round 2/3-Group 1 u_agent 1 proposition: [76, 96] backed ranges: [0/1][3/4] → broaden range → final proposal 73 u_agent 2 proposition: [59, 71] backed ranges: [0/1][4/4] → forward proposition…”
mentioning
confidence: 99%
“…The aim of an ambient intelligent system is to provide comfortable assisted living to inhabitants. Scientific work has been done in ambient intelligent space such as Care-lab, CASAS, Grator-Tech HIS, aware home, iDorm and MavHome projects, the process of activity recognition is subdivided into four part as (i)sensing, (ii)data-preprocessing, (iii)data modelling for feature extraction (iv)feature selection [1]. Many blue-chip companies including IBM Watson, researching into identifying inhabitants preference, activity patterns to provide a customized digital assistant for granting access and controlling various appliance to automated tasks [2].…”
Section: Introductionmentioning
confidence: 99%
“…HMM is a generative probabilistic model used for identifying hidden states <s1,s2,..,sn>from given observation sequences<o1,o2,..on> [3]. Furthermore, [1] suggested that observable state sequence(st1) at time t , depends only on the current state(st), irrespective of previous state (st -1).During HMM training we tend to find optimal state sequence with higher probability of Pr(S|O), 1 1 DOI reference number: 10.18293/SEKE2017-035 known as most likelihood pattern. As an iterative trend, HMM require re-estimation of input parameters to train the system (transition and emission matrix), Baum-welch algorithm work well here as solution.…”
Section: Introductionmentioning
confidence: 99%